Alternative Large-Scale Conservation Visions for Northern Maine: Interviews with Decision Leaders in Maine - Baldwin, Elizabeth; Kenefic, Laura; LaPage, Will (Maine Policy Review, 2007)
Based on confidential interviews with 21 decision leaders in Maine, Elizabeth Baldwin, Laura Kenefic, and Will LaPage examine the complexity of the conflicts over alternate visions for large-scale conservation in Maine. Exploring models that may be useful for policymakers grappling with competing values for Maine’s forests, they present four alternatives: national forests, new U.S. forest service models, forest heritage areas, and the British national park model. The authors found that the leaders interviewed agreed about the need for some level of conservation, but did not completely agree on how this might happen and where the decision-making power should lie.
Keywords: Maine; conservation; land-use planning; forests